Complement Evasion Contributes to Lyme Borreliae–Host Associations. Issue 7 (July 2020) - Lin, Yi-Pin; Diuk-Wasser, Maria A.; Stevenson, Brian; Kraiczy, Peter
Abstract : Lyme disease is the most common vector-borne disease in the northern hemisphere and is caused by spirochetes of the Borrelia burgdorferi sensu lato complex. Lyme borreliae infect diverse vertebrate reservoirs without triggering apparent manifestations in these animals; however, Lyme borreliae strains differ in their reservoir hosts. The mechanisms that drive those differences are unknown. To survive in vertebrate hosts, Lyme borreliae require the ability to escape from host defense mechanisms, in particular complement. To facilitate the evasion of complement, Lyme borreliae produce diverse proteins at different stages of infection, allowing them to persistently survive without being recognized by hosts and potentially resulting in host-specific infection. This review discusses the current knowledge regarding the ecology and evolutionary mechanisms of Lyme borreliae–host associations driven by complement evasion. Highlights: Emerging and re-emerging zoonotic diseases have a major impact on global public health, including tick-transmitted illnesses such as Lyme disease. Lyme disease-causing pathogens develop a range of sophisticated strategies to overcome the innate immune system of various vertebrate hosts to accomplish their –enzootic cycle. Inactivation of the host´s complement in the tick's blood meal, and in the host's bloodstream, are crucial steps to prevent the spirochetes from being killed during their transmission and dissemination. Strain-to-strain variation in the spirochetes' ability to evade complement may contribute to variation in the range of Lyme borreliae–host associations.